Work Roles in Human–Robot Collaborative Systems: Effects on Cognitive Ergonomics for the Manufacturing Industry - Pablo Segura; Odette Lobato-Calleros; Isidro Soria-Arguello; Eduardo Gamaliel Hernández-Martínez (Applied Sciences)
Human–robot collaborative systems have been adopted by manufacturing organizations with the objective of releasing physical workload to the human factor. However, the roles and responsibilities of human operators in these semi-automated systems have not been properly analyzed. This might carry important consequences in the cognitive dimension of ergonomics, which then contradicts the main well-being goals of collaborative work. Therefore, we designed a series of collaborative scenarios where we shifted the assignment of work responsibilities between humans and robots while executing a quality inspection task. Variations in the state of cognitive ergonomics were estimated with subjective and objective techniques via workload tests and physiological responses respectively. Furthermore, we introduced a work design framework based on 50 state-of-the-art applications for a structured implementation of human–robot collaborative systems that contemplates the underlying organizational and technological components necessary to fulfill its basic functionalities. Human operators that possessed responsibility roles over collaborative robots presented better results in terms of cognitive workload and spare mental capacity alike. In this regard, mental demand is seen as a key workload variable to consider when designing collaborative work in current manufacturing settings.